Less wound complications of a sinus tarsi approach compared to an extended lateral approach for the treatment of displaced intraarticular calcaneal fracture: A randomized clinical trial in 64 patients. Issue 36 (September 2016) - Li, Lian-hua; Guo, Yong-zhi; Wang, Hao; Sang, Qing-hua; Zhang, Jian-zheng; Liu, Zhi; Sun, Tian-sheng
Abstract: Background: We conducted a prospective randomized clinical trial to compare the clinical and radiological outcomes of the sinus tarsi and extended lateral approaches for the surgical treatment of displaced intraarticular calcaneal fractures. Methods: Between January 2009 and January 2014, patients with displaced intraarticular calcaneal fracture were randomly assigned to receive surgical treatment by the sinus tarsi approach or the extended lateral approach using block randomization. We recorded and analyzed data on demographics, time to surgery, wound complications, Böhler angles pre- and postoperatively, and American Orthopedic Foot & Ankle Society score. Results: Sixty-four patients met the inclusion criteria and were randomly assigned to the 2 groups: 32 patients underwent sinus tarsi approach, and 32 patients the extended lateral approach. Baseline characteristics of both groups were similar. The time to surgery in the sinus tarsi approach group was significantly shorter than in the extended lateral approach group ( P = 0.04). The wound complication rates were 6.3% and 31.2% in the sinus tarsi approach and extended lateral approach groups, respectively, which was significantly different ( P = 0.01). Regarding the clinical outcomes, the groups did not differ significantly on walking visual analogue scale or American Orthopedic Foot & Ankle Society scores at 6 months and 1 year postoperatively. No significant differences existed between groups regarding the Böhler angle at different times and reduction quality of the articular surface and the medial wall. Conclusion: Compared with the extended lateral approach, the sinus tarsi approach decreased wound complications and preoperative waiting time, and achieved similar functional and radiological outcomes for displaced intraarticular calcaneal fractures.